Search for long-lived particles decaying to jet pairs - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (The European physical journal. C, Particles and fields, 2015)
A search is presented for long-lived particles with a mass between 25 and 50 $$\mathrm{GeV}/\mathrm{c}^{2}$$and a lifetime between 1 and 200$$\mathrm{\,ps}$$in a sample of proton-proton collisions at a centre-of-mass energy of $$\sqrt{s}=7$$ TeV, corresponding to an integrated luminosity of 0.62 $$\text{ fb }^{-1}$$, collected by the LHCb detector. The particles are assumed to be pair-produced by the decay of a standard model-like Higgs boson. The experimental signature of the long-lived particle is a displaced vertex with two associated jets. No excess above the background is observed and limits are set on the production cross-section as a function of the long-lived particle mass and lifetime.